The mystery of the missing P waves: a case report - Yuanguo Chen; Haibo Zhang; Changli Han; Peng Bai (Journal of Medical Case Reports)
Abstract Background This case highlights the diagnostic challenges of atrial flutter with concealed atrial activity on surface electrocardiograms, emphasizing the necessity of invasive electrophysiological study to avoid unnecessary pacemaker implantation in patients with structural heart disease—a scenario rarely documented in current literature. Case presentation A 60-year-old ​Chinese woman with rheumatic mitral stenosis and prior maze procedure presented with fatigue and bradycardia (heart rate, 47 beats per minute). Surface electrocardiograms (including modified Lewis leads) revealed no discernible P waves, while echocardiography demonstrated atrial mechanical silence. Electrophysiological study identified cavotricuspid isthmus-dependent atrial flutter with extensive right atrial low-voltage zones (voltage < 0.5 mV), explaining the absent surface atrial activity. Radiofrequency ablation achieved bidirectional isthmus block, restoring sinus rhythm (heart rate, 59 beats per minute) without pacemaker requirement. Conclusion In patients with bradycardia and electromechanical atrial dissociation, electrophysiological study proves indispensable for detecting atrial flutter obscured by severe fibrosis. This approach prevents inappropriate pacemaker implantation while restoring physiological rhythm, establishing a paradigm for managing complex arrhythmias in structural heart disease.